Induction of New Lactam Derivatives From the Endophytic Fungus Aplosporella javeedii Through an OSMAC Approach - Gao, Ying; Stuhldreier, Fabian; Schmitt, Laura; Wesselborg, Sebastian; Guo, Zhiyong; Zou, Kun; Mándi, Attila; Kurtán, Tibor; Liu, Zhen; Proksch, Peter (Frontiers in Microbiology, 2020)
Fermentation of the endophytic fungus Aplosporella javeedii on solid rice medium in presence of either 3.5% NaNO3 or 3.5% monosodium glutamate caused a significant change of the fungal metabolite pattern compared to fungal controls grown only on rice. Chemical investigation of the former fungal extracts yielded 11 new lactam derivatives, aplosporellins A–K (2–12), in addition to the known compound, pramanicin A (1). All of these compounds were not detected when the fungus was grown on rice medium without these activators thereby indicating the power of this OSMAC approach. The structures of the new compounds were elucidated by one- and two- dimensional NMR spectroscopy, DFT-NMR calculations and by mass spectrometry as well as by comparison with the literature whereas the absolute configuration of the lactam core was determined by TDDFT-ECD and OR calculations. Pramanicin A (1) showed strong cytotoxicity against human lymphoma (Ramos) and leukemia (Jurkat J16) cells with IC50 values of 4.7 and 4.4 μM, respectively. Mechanistic studies indicated that 1 activates caspase-3 and induces apoptotic cell death.